A solid-state fault current limiting and interrupting device (FCLID) with power factor correction - Paterakis, Fotis; Marouchos, Christos; Putrus, Ghanim A.; Darwish, Mohamed; Makarounas, Christos (My University, 2018)
A Solid-State Fault Current Limiter and interrupting device (FCLID) with power factor correction suitable for low-voltage distribution networks employing the Switched Capacitor (SC) Circuit is presented. Some design parameters are investigated and some optimisation is applied. In this application the Switched Capacitor (SC) is inserted in series with the supply line via an isolating transformer, providing both power factor correction and limitation of the current to a pre-set value in the event of a fault. Interruption of the fault is also possible by setting both semiconductor switches in the off state. The voltage across the load is increased. Optimisation is applied to correct the power factor to an acceptable value of 0.85 and keep the load voltage within acceptable limits. Losses are estimated and rating of components is discussed.
Keywords: Current limiter; Distribution network; Duty cycle; Power factor; Switched capacitor